The Effect of Hip Flexor Tightness on Muscle Activity during the Front Squat - Sarah C. Martinez-Sepanski; Angie Bowman; Ketlon Mehls (International Universities Strength and Conditioning Association, 2024)
The purpose of this study was to compare peak and mean surface electromyography (sEMG) in the rectus femoris (RF), gluteus maximus (GM), biceps femoris (BF), semitendinosus (ST) muscles, and GM:BF muscle co-activation ratio during front squat between resistance trained females with and without hip flexor tightness. Peak and mean sEMG was recorded during three repetitions of 75% of one-repetition maximum (1RM) front squat of resistance trained females who either had hip flexor tightness (n = 9) or did not have hip flexor tightness (n = 7). Observed mean sEMG of the GM and BF was used to calculate GM:BF muscle co-activation. The result of the independent samples t-test indicated a statistically significant difference in peak RF (p = .013), peak (p = .001) and mean (p = .045) BF, and GM:BF muscle co-activation (p = .042) between those with and without hip flexor tightness during the ascending phase of a 75% 1RM front squat. The results indicate the RF and BF to be more active in resistance trained females with hip flexor tightness than those without hip flexor tightness during the front squat, potentially lowering GM activation relative to the BF. Fitness professionals should consider providing a hip flexor stretching interventions to prevent over activation of the BF when selecting the front squat as a resistance training exercise.